Fertility in North Sumatera: Why is it not declining? (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
The results of the Indonesia Demographic and Health Survey (IDHS) in 2017 confirm that although the prevalence of contraception is quite high, the fertility rate in North Sumatera Province is still high. Fertility decomposition analysis has been used extensively to identify changes in fertility in various countries. This study was conducted to determine the pattern of changes in fertility decomposition in North Sumatra by using IDHS data in 2002/03 and 2017. The total fertility rate (TFR) from 2002 to 2017 in this province relatively remains the same, which is around 3 children per woman. There was a change in the proximate contribution of the determinant of fertility. Contraceptive use and effectiveness are the main contributors affecting the fertility rate in North Sumatra Province. The contribution of breastfeeding patterns has increased and marital patterns have decreased over a period of 15 years. The implementation of population and family planning programs in North Sumatra Province needs to be continuously improved to reach a TFR of 2.1 children per woman by 2024. Promotion of exclusive breastfeeding needs to be encouraged to extend the birth interval and reduce natural fertility. Prevention programs for child marriage and teenage pregnancy should be promoted.